2006
DOI: 10.1111/j.1399-3046.2006.00580.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term evaluation of cyclosporine and tacrolimus based immunosuppression in pediatric liver transplantation

Abstract: Both calcineurin inhibitors (CNIs), cyclosporine and tacrolimus, are widely used in pediatric liver transplant recipients and currently data are limited with regards to long-term results using the one drug or the other in comparable low doses. We conducted the present study to assess the advantages and disadvantages of both drugs in children at least five yr post-liver transplantation. A total of 129 children were enrolled in the study. Thirty-eight of the children were switched to tacrolimus monotherapy for d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 19 publications
0
21
0
1
Order By: Relevance
“…Fifty percent of the 16 studies included in this review relied on the use of antihypertensive medications as evidence of hypertension, and 13% provided no definition 22, 23, 27, 33‐45. Estimates of the prevalence of hypertension from these studies vary from 4% to 100% (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fifty percent of the 16 studies included in this review relied on the use of antihypertensive medications as evidence of hypertension, and 13% provided no definition 22, 23, 27, 33‐45. Estimates of the prevalence of hypertension from these studies vary from 4% to 100% (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Six studies (37%) applied age‐ and sex‐specific BP percentiles in addition to medication regimens. Three of the 4 studies that used percentiles to report the prevalence of hypertension 5 to 10 years after transplantation estimated the prevalence to be 20% to 28%27, 33, 40; 1 study reported a lower prevalence 34. The 2 studies that reported hypertension 1 year after transplantation estimated a prevalence of 58% to 64%, although the majority of these children were receiving CSA 35, 36.…”
Section: Resultsmentioning
confidence: 99%
“…CsA and TAC serve as a cornerstone of immunosuppressive regimens in pediatric solid organ transplantation [5]. Both drugs have similarity of mode of action, efficacy, and side effects; however, they are chemically unrelated and have certain differences affecting the choice of either of them in immunosuppressive treatment [5,6].…”
Section: Metabolism and Transport Of Calcineurin Inhibitorsmentioning
confidence: 99%
“…Both drugs have similarity of mode of action, efficacy, and side effects; however, they are chemically unrelated and have certain differences affecting the choice of either of them in immunosuppressive treatment [5,6].…”
Section: Metabolism and Transport Of Calcineurin Inhibitorsmentioning
confidence: 99%
“…CNI share a number of side effects in common including nephrotoxicity, neurotoxicity, and hyperlipidemia [57]. There are, however, some differences between tacrolimus and cyclosporin.…”
Section: Postoperative Ismentioning
confidence: 99%